Concentrations and diffusion coefficients of thermal equilibrium point defects in silicon crystals. (1st July 2022) - Suezawa, Masashi; Iijima, Yoshiaki; Yonenaga, Ichiro
Abstract: The dependencies of concentrations of thermal equilibrium vacancies and interstitials on temperatures in Si crystals are determined directly, which has been a long-standing issue since the 1950s. They are evaluated by combining the formation energies and self-diffusion entropies deduced from the analyses of self-diffusion coefficients, and migration entropies deduced from diffusion coefficients of point defects. The concentrations as the number density of thermal equilibrium vacancies and interstitials at temperature T (K) are determined to be 5 × 10 22 exp(6.5)exp(–3.85 eV/ k B T ) and 5 × 10 22 exp(10.6)exp(–4.3 eV/ k B T ) cm −3, respectively. The diffusion coefficients of vacancies and interstitials are determined to be 2.7 × 10 −3 exp(–0.45 eV/ k B T ) and 2.5 × 10 −2 exp(–0.49 eV/ k B T ) cm 2 s −1, respectively. The results are discussed in comparison with those reported experimentally.